Response of two rice (Oryza sativa) hybrids to graded levels of nitrogen - OM, HARI; KATYAL, S K; DHIMAN, S D (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during was season of 1993 and 1994 to study the effect of 5 nitrogen levels (0,50,100, 150 and 200 kg/ha) and 2 rice (Oryza sativa) hybrids' PHB 71 ' and 'PMS2A/IR31802'). The results revealed thatthe hybrid I PHB 71' seed lings were more vigorous than the 'PMS2A/IR31802' in terms of dry weight, shoot length andvigour index. There was a significant increase in grain yield with each additional application of nitrogen from 0 - 200 kg/ha during 1993 while in 1994 the increase in N dose from 150 - 200 kg/ha could not register significant increase. Hybrid'PHB 71 'gave 0.75 and 0,95 tonnes/ ha higher yield than' PMS2A/IR31802' in 1993 and 1994 respectively. The highestlevel of yield 9.25 and 8.24 tonnes/ha was recorded by 'PHB 71 ' at 200 kg N/ha during the respective year. Yield attributesshowed improvement with the increase in N level.